2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27669
|View full text |Cite
|
Sign up to set email alerts
|

Board # 101 :Impact of a Year-round Out-of-School Maker Program on Minority Middle School Boys (Work in Progress)

Abstract: Male Maker Program, which focuses on providing minority middle school boys with hands-on learning experiences using advanced technology, app development software, 3-D design techniques, and entrepreneurship skills. Mrs. Partlow also serves as the Lab Manager of the Engineering Visualization Research Laboratory (EVRL) where she helps to advise students on undergraduate electrical engineering research projects ranging from smart lighting technologies to cyber security. She has also served as an online course dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The Maker movement has made significant progress in the informal field of STEM education (Ladeji-Osias & Partlow, 2017). National Research Council (2015) has also indicated that becoming productive from out of school learning opportunities for young people is a key part of the STEM learning ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The Maker movement has made significant progress in the informal field of STEM education (Ladeji-Osias & Partlow, 2017). National Research Council (2015) has also indicated that becoming productive from out of school learning opportunities for young people is a key part of the STEM learning ecosystem.…”
Section: Introductionmentioning
confidence: 99%